KARAKTERISASI OPTIK DAN SIFAT LISTRIK FILM LiTaO3 PADA VARIASI SUHU ANNEALING - Ira Ukhtianingsih; Yulia Sani; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
LiTaO3 thin films has been grown upper side on p-type Si (100) substrates using Chemical Solution Deposition (CSD) methods followed by spin coating its speed 3000 rpm with dropped for 30 seconds in solubility 1 M. Thin films was annealed at 550 ËšC, 575 ËšC, 600 ËšC and 625 ËšC with increasing degree of annealed 1.67 ËšC/minutes. This conductivity values is semiconductor and conductivity. It might be effect the result of optical test showed LiTaO3 thin films could absorb in UV wavelength. It is convincing that LiTaO3 promise to be used for infrared sensor. Keywords: conductive, LiTaO3, optical, p-type silicon, semiconductor.